Improvement and Uncertainties of Global Simulation of Sulfate Concentration and Radiative Forcing in CESM2. Issue 20 (17th October 2022) - Ge, Wendong; Liu, Junfeng; Xiang, Songlin; Zhou, Yuhan; Zhou, Jingcheng; Hu, Xiurong; Ma, Jianmin; Wang, Xuejun; Wan, Yi; Hu, Jianying; Zhang, Zhaobin; Wang, Xilong; et al.
Abstract: Sulfate is a major atmospheric pollutant and radiative forcing (RF) factor that influences air quality, cloud microphysics, and climate. Therefore, a better evaluation of sulfate concentrations and RF patterns is essential for policy‐making and the management of air pollution and climate change. This study comprehensively estimates the global distribution of sulfate concentrations and RFs and analyzes the sources of uncertainty in the Community Earth System Model version 2 and the Parallel Offline Radiative Transfer model. Compared with the observations, the incorporation of detailed in‐cloud aqueous‐phase chemistry and the enhanced wet deposition (WD) flux of sulfate significantly improved the simulations of sulfur species both near the ground and at high altitudes, which is beneficial for a more accurate estimation of the global RF of sulfate. The improved simulated RF of sulfate from 1850 to 2015 is −0.502 Wˑm −2 . This study finds that WD is the key process governing both the horizontal and vertical distributions of sulfate concentrations. The overestimation of surface sulfate and the underestimation of high‐altitude sulfate made by the model are essential uncertainty factors of the sulfate RF estimation. This study emphasizes the importance of improving the simulation of global sulfate distribution as well as its RF, which may strongly pressure the near‐future warming potential when witnessing a rapid transition to a carbon neutral world that is phasing out fossil fuel. A more accurate assessment of sulfate levels and radiation effects will play a remarkable guiding role in the formulation of global emission reduction‐related policies in the future. Plain Language Summary: Sulfate aerosols play an essential role in the entire atmosphere and climate system. Therefore, it is necessary to better simulate the distribution and radiative forcing (RF) of sulfate. By using a global climate model, we improved the simulation of sulfate distribution both near the ground and at high altitudes and achieved a more accurate estimation of the global RF of sulfate. We found that wet deposition is the key process influencing the distribution of sulfate concentrations. The overestimation of surface sulfate and the underestimation of high‐altitude sulfate are important uncertainty factors of sulfate RF. Our results suggest that more field studies (e.g., aircraft campaigns, surface measurements over remote regions, etc.) of sulfate are urgently needed. This study indicates that large uncertainties may exist in current global climate models, which may impact the formulation of future policy‐making in carbon neutrality. Key Points: The global simulations of sulfate distribution and radiative forcing are significantly improved with the usage of Community Earth System Model version 2 Wet deposition is the key process governing both the horizontal and vertical distributions of global sulfate concentrations The uncertainty of sulfate forcing is very important to the formulation of global carbon neutral policies